EFEKTIVITAS PROGRAM KUNJUNGAN RUMAH MASYARAKAT HIDUP SEHAT (KURMA MANIS) DI KOTA PEKANBARU TAHUN 2023-2024 - Jihani, Syavira; Pane, Rico Purnawandi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2026)
The Community Healthy Living Home Visit Program (Kurma Manis) is a health service innovation implemented by the Pekanbaru City Government with the objective of improving access to and quality of health services, as well as accelerating service response time for the community. However, in its implementation, several challenges remain, including limited public awareness of the program, inadequate dissemination of information, complicated service procedures, and relatively slow service responses. In addition, the limited availability of healthcare personnel and the lack of optimal monitoring and evaluation have also hindered the effective implementation of the program. The research aims to analyze the effectiveness of the Kurma Manis Program in Pekanbaru City during the 2023–2024 period by applying Budiani’s program effectiveness theory. The analysis focuses on four main indicators, namely target accuracy, program socialization, achievement of program objectives, and monitoring and evaluation. The research employs a qualitative approach, with data collection techniques including interviews, observations, and documentation. The informants involved in this research consist of representatives from the Pekanbaru City Health Office and several public health centers participating in the implementation of the Kurma Manis Program. The data analysis technique employed in this study utilizes the interactive analysis model developed by Miles dan Huberman, which encompasses the stages of data reduction, data display, data verification, and conclusion drawing. The findings indicate that the implementation of the Kurma Manis Program has been carried out; however, it has not yet been fully effective. This is reflected in the limited dissemination of the program to the community, suboptimal coordination among implementers, as well as constraints related to budget allocation and human resources. The implementation of the Kurma Manis Program continues to face several challenges that affect its overall level of effectiveness. Certain aspects of the program have not yet been optimally implemented, resulting in the program objectives not being fully achieved. Therefore, improvements are necessary in the implementation of the program to enhance its effectiveness and ensure greater benefits for the community. Keywords: Program Effectiveness, Kurma Manis Program, Health Services